Coordination of pumped-storage unit and irrigation system with intermittent wind generation for intelligent energy management of an agricultural microgrid. (1st January 2018) - Ghasemi, Ahmad
Abstract: This paper presents a new coordination framework to optimize the joint operation of pumped-storage unit, irrigation system and intermittent wind power generation in an agricultural microgrid. The microgrid is an agricultural complex connected to the medium voltage network. This complex contains a farm needing water to be irrigated every day. The irrigation system has two large scale reservoirs located in different levels. These reservoirs have been planned to act as pumped-storage unit reservoirs. The microgrid contains different electrical loads such as industrial livestock, agricultural products packaging factory, drip irrigation system, lighting and other small loads. The microgrid is connected to the upstream network at the grid supply point (GSP) and supplies loads with power from the upstream network and a wind power unit located in the farm. The proposed framework optimizes day-ahead (DA) scheduling of power exchange with the upstream network, pumped-storage unit and irrigation system based on forecasted wind power, microgrid load demand and water needed for irrigation in a market environment. The two-point estimate method (TPEM) is implemented to model the uncertainties associated with wind power and wholesale market prices. Finally, the effectiveness of the proposed framework is evaluated on several case studies. Highlights: Energy and water resources are simultaneously managed in an agricultural microgrid. . The joint operation of irrigation system, pumped-storage unit and wind power is studied. The inherent uncertainty of wind power and market prices are considered.